Short Communication: Comparing the growth of stem explants between Citrus reticulata var. Tawangmangu and C. reticulata var. Garut using in vitro culture methods - Erma Prihastanti; ENDAH D. HASTUTI; SRI W.A. SUEDY (Society for Indonesian Biodiversity, 2020)
Abstract. Prihastanti E, Hastuti ED, Suedy SWA. 2020. Short Communication: Comparing the growth of stem explants between Citrus reticulata var. Tawangmangu and C. reticulata var. Garut using in vitro culture methods. Biodiversitas 21: 5845-5849. Several efforts have been made to preserve Citrus reticulata var. Tawangmangu and Citrus reticulata var. Garut as indigenous Indonesian mandarin cultivars, including in vitro tissue culture methods. This study aimed to determine growth differences of the stem explants of C. reticulata var. Tawangmangu and C. reticulata var. Garut,which planted on the same Murashige and Skoog (MS) media. The treatment groups were derived from different explants, grown in 4 separate culture bottles for 35 days at 25°C. The observed parameters included the percentage of explants indicating callus development browned-colored explants, and the contaminated explants. Among C. reticulata var. Tawangmangu explants, 23.53% indicated callus development, 29.42% were browned-colored explants, and 0% indicated contamination. In contrast, among the C. reticulata var. Garut explants, 0% indicated callus development, 7.14% brown-colored, and 7.14% indicated contamination. The stems explants from C. reticulata var. Tawangmangu showed a tendency to develop calluses, but the explants of C. reticulata var. Garut was able to support the growth of shoots. C. reticulata var. Tawangmangu and Garut mandarin stem explants showed differences of shoot growth because physiological conditions varied according to the variety.